HIV Alters Gap Junction-Mediated Intercellular Communication in Human Brain Pericytes - Cho, Hyung Joon; Kuo, Alyce Mei-Shiuan; Bertrand, Luc; Toborek, Michal (Frontiers in Molecular Neuroscience, 2017)
Despite successful control of viremia by combined antiretroviral therapy, brain infection and its resulting neurocognitive impairment remain a prevalent comorbidity in HIV infected individuals. HIV invades the brain early in the course of infection via penetration through the blood-brain barrier (BBB). While the impact of HIV on BBB astrocytes and endothelial cells is relatively well studied, the role of pericytes in BBB regulation during HIV infection remains unclear; however, it is known that a selective population of pericytes is prone to infection. In the present study, we hypothesize that injury signals are propagated from infected pericytes to neighboring cells via gap junction (GJ)-mediated intercellular communication. Among a variety of studied GJ proteins, HIV infection of human brain pericytes specifically increased expression of connexin 43 as determined by immunoblotting and immunostaining. This effect was confirmed in the brains of mice infected with EcoHIV, a mouse-specific HIV strain. In addition, HIV infection enhanced functional GJ-mediated intercellular communication in pericytes. The importance of this process was confirmed in experiments in which inhibition of GJs by carbenoxolone attenuated HIV infection. In addition to GJs, an extracellular ATP release assay revealed that HIV may also play a role in opening of connexin (Cx)-containing hemichannels. Overall, these findings indicate an important role of GJs in the propagation of HIV infection in human brain pericytes that may contribute to BBB dysfunction in brain infection and the pathogenesis of NeuroAIDS.